Exclusive breastfeeding and women's psychological well-being during the first wave of COVID-19 pandemic in Italy - Ravaldi, Claudia; Mosconi, Laura; Wilson, Alyce N.; Amir, Lisa H.; Bonaiuti, Roberto; Ricca, Valdo; Vannacci, Alfredo (Frontiers in Public Health, 2022)
Background At the onset of the COVID-19 pandemic, support for breastfeeding was disrupted in many countries. Italy was severely impacted by the pandemic and is known to have the lowest exclusive breastfeeding rate of all European countries. Considering the inverse association between anxiety and breastfeeding, maternal concerns about the COVID-19 emergency could reduce breastfeeding rates. The aim of the study is to explore the association between infant feeding practices and maternal COVID-19 concerns. Methods This paper is a secondary analysis of the cross-sectional study COVID-ASSESS conducted in Italy in 2020. The original survey was administered in two phases: during the first lockdown and during the reopening. The survey included five sections: socio-demographic, medical history, concerns about the COVID-19 pandemic, infant feeding practices and psychometric evaluation. Participants were considered eligible for the post-hoc analyses if they were exclusively breastfeeding or they were feeding with infant formula (either alone or with breastfeeding) at the time of the interview. Results Between phase 1 and phase 2 there was a decrease in anxiety and concerns about the danger of COVID-19 to general health, except for concerns about their baby’s health. Women using formula were more concerned about all the health topics investigated. Moreover, they showed higher levels of stress, state anxiety, somatization and PTSD symptoms. Conclusion Breastfeeding during the first pandemic lockdown in Italy seems to have been an independent factor associated with lower anxiety about COVID-19, fewer psychopathological symptoms, and a positive experience of infant feeding.